Leadership in human resources management system - Stetsiuk, Y.; Trygub, Inna (My University, 2015)
Leadership can be defined as based on the authority and rank priority ongoing impact of one person or a few individuals to the whole group or organization.
Keywords: leadership; person; лідерство; кафедра ділової іноземної мови та міжнародної комунікації